Using SWAT Model to Estimate the Water Balance of Wadi Al-Mohammadi Basin, Western Iraq: Setup of SWAT Model, SWAT Model Run, Watershed Delineation, Climate Data, Quantification of Hydrological Components, and Water Balance of the Wadi Al-Mohammadi Basin. - Al-Kubaisi, Mahmood H. D.; Al-Kubaisi, Qusai Y. S. (Iraqi Journal of Science, 2023)
Water balance as a technique is considered one of the means that is relied upon in solving significant hydrological problems. The soil and water assessment tool (SWAT) model was used in this study to assess the water balance in the Wadi Al-Mohammadi basin located at the eastern edge of the Western Desert. Digital elevation model, soil data, Land use - Land cover, and climate data represent the most important requirements for the SWAT model's input as a database. The Wadi Al-Mohammadi basin delineation results show the overall drainage area was 2286.8 km2 with seven sub-basins. The trend line of climate data indicates a clear increase in the total rainfall, relative humidity, temperature, and solar radiation from 1990-2020, while the wind speed decreased during the observed period. The average monthly hydrological components (precipitation, actual evapotranspiration, surface runoff, lateral flow, and deep aquifer recharge) representing the basin's water balance are 68.8 mm, 67 mm, 2.03 mm, 0.02 mm, and 0 mm, respectively.